PENGARUH MUTASI DAN BEBAN KERJA TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA KARYAWAN KANTOR KPU KABUPATEN PROBOLINGGO - Tumini Tumini; Jonni Hendra; Yusroniah Yusroniah (STIE Mandala Jember, 2022)
This study aims to determine the effect of mutations and workload on performance with motivation as an intervening variable on employees KPU Office Probolinggo Regency. This type of research uses a survey method and causal associative. The population is the employees KPU Office Probolinggo Regency. The sample is taken using technique saturated sampling as many as 30 respondents. The method of analysis using statistical test and path analysis. The research results of hypothesis testing show that mutations have a positive and significant effect on performance, workload has a negative and significant effect on performance, mutations have a positive and significant effect on motivation, workload has no effect on motivation, motivation has a positive and significant effect on performance, mutations have a positive and significant effect on performance through motivation, and workload have no effect on performance through motivation. Therefore, the agency is expected to maintain and increase motivation for employees so that employee performance can increase and produce good quality work. Keywords: Workload, Performance, Motivation, Mutations, Intervening Variables